2015
DOI: 10.1016/j.proche.2015.12.076
|View full text |Cite
|
Sign up to set email alerts
|

Stability Study of Betacyanin Extract from Red Dragon Fruit (Hylocereus Polyrhizus) Peels

Abstract: The purpose of this study was to determine the effect of alginate and CaCl2 concentration of antioxidant activity and betacyanin content of restructuring product of red dragon fruit, and to determine the best formulation of the product restructuring that produces antioxidant activity and the content of the highest betacyanin on product restructuring. Data were analyzed by 4x2 Factorial Design and Randomized Completely Block Design (RCBD) with 4 replications. As the first factor is the alginate concentration wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 1 publication
0
42
1
1
Order By: Relevance
“…The content of betacyanins was 9.22 mg g −1 dry sample, which was higher than 185.5 mg/100 g (Stintzing et al ., ) and 515.20 μg/100 g extracted by methanol (Priatni & Pradita, ). From the HPLC of Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The content of betacyanins was 9.22 mg g −1 dry sample, which was higher than 185.5 mg/100 g (Stintzing et al ., ) and 515.20 μg/100 g extracted by methanol (Priatni & Pradita, ). From the HPLC of Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The degradation kinetic models of APS, LPS and PCPS were tnormalAPS=lnA0-lnA8.98×104×expfalse(-4555false/Tfalse),tnormalLPS=lnA0-lnA24.08×exp(-1997/T),tnormalPCPS=lnA0-lnA6.16×106×expfalse(-6021false/Tfalse). A recent paper showed that the equation of linear squares data of betacyanins in dragon fruit peels was y = −7231 x + 1668 (Priatni & Pradita, ), which was different from our equation: y APS = −4555.1 x + 11.405. Some studies reported increasing betalain degradation rates resulting from increasing temperature, that is the longer the exposure time was, the more serious degradation was (Mello et al ., ; Xu et al ., ; Song et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that dragon fruit byproducts have a high concentration of different bioactive compounds. Priatni and Pradita () found that acidified methanol allowed a higher extraction of betacyanins from peels (515 µg per 100 g FW), compared with the extraction yield of acidified water (491 µg per 100 g FW). Moreover, the stability of the extracted betacyanin was higher in the organic extract after five hours storage at room temperature.…”
Section: Wastes and Byproducts From Tropical Fruits And Their Currentmentioning
confidence: 99%